Optimizing employee performance in Jabatan Ketua Menteri Melaka / Mohammad Haiqal Hashim - Hashim, Mohammad Haiqal (Faculty of Business and Management, 2019)
The purpose of this research was to study about Optimizing Employee Performance in Jabatan Ketua Menteri Melaka. There were three factors involved: training and development, performance appraisal system and employee involvement and its influence on employee performance. The questionnaire were distributed to 169 staff of Jabatan Ketua Menteri Melaka and the results analysed using SPSS. The results show that there is a relationship between training and development and employee involvement on employee performances, but not to performance appraisal.